The Bratsk Organization of the Union of Architects of Russia: A Short Excursion to the History - Astrakhantseva, Victoria (project baikal, 2015)
The article presents the history of the Bratsk Organization of the Union of Architects of Russia, from formation of the Bratsk Branch of the Union of Architects of the USSR in 1974 and its transformation into an independent organization in 1992, until the present time.